›Amicus Lucretius‹ Gassendi, il ›De rerum natura‹ e l'edonismo cristiano - Piergiacomi, Enrico (CICERO - STUDIES ROMAN THOUGHT RECEPTION OA, 2022)
The book provides the first systematic reconstruction of the reception of Lucretius' theological and ethical verses in the work of the early modern philosopher Pierre Gassendi (1592-1655). It argues that the latter was the first to quote and discuss almost the entire De rerum natura, intending to develop a modified version of Epicurean philosophy, compatible with the new science and the religious/ethical demands of Christianity.